A Tribute to Those Who Helped Me Get Here - Barry S. Schermer (Washington University Journal of Law & Policy, 2017)
This Article includes personal reflections from United States Bankruptcy judge for the Eastern District of Missouri and judge for the Bankruptcy Appellate Panel for the Eighth Circuit Judge Barry S. Schermer after 30 years of judicial service. Judge Schermer recalls his days as a practitioner and bankruptcy trustee, which shaped his interests toward applying for his first judgeship. Judge Schermer also recognizes the co-teachers, legal clerks and interns, and support staff that have filled his decades of jurisprudence and scholarship.
Keywords: Judge Schermer